Speech text of International Day of Mathematics (IDM) 2023 / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
I am here on behalf of the Vice-Chancellor, Prof. Datuk Ts. Dr Hajah Roziah Mohd Janor, who could not be with us today. She sends her warmest regards to all present, especially to all mathematicians and mathematics enthusiasts on this International Day of Mathematics (IDM). In 2019, UNESCO inaugurated March 14 as the International Day of Mathematics in reference to the date resembling the Pi ( ) Number - 3.14 which is used toπ calculate the circle area that can be traced back to the ancient Babylonians from four centuries ago. 4. Not only that but March 14 is also the birthdate of Albert Einstein. Sadly, in the world of progress, it also marks the death of Stephen Hawking. These individuals have contributed massive remarkable discoveries in the study of the universe using mathematical physics. This is why today we celebrate and acknowledge the essential role mathematics plays in various aspects of our lives.